DEFORMATION ANALYSIS AND EXPERIMENTAL VERIFICATION OF HAT⁃TYPE FLEXSPLINE UNDER NO LOAD - XU ShaoYan; LI GuoPing; CEN GuoJian; HUANG Bing; LUO LiMin; LOU JunQiang (Jixie qiangdu)
As the core component of the harmonic reducer,the contact stress and deformation distribution during the assembly process of the flexispline affect the reliability life.The finite element assembly simulation process analysis was carried out by using hat⁃type flexispline,and the deformation and stress analysis of the long and short shafts of the flexispline and the front and rear end of the ring gear were extracted respectively.The results show that the deformation at the long axis and the short axis show a linear decrease trend in line with the actual situation,and the deformation of the front and rear end of the ring gear changes periodically.The equivalence stress shows a downward trend in the axial tooth width part of the major and minor axes.The large equivalence stress at the front and rear end of the ring gear is generated at the long and short axes,while the maximum equivalence stress appears in the transition zone at the bottom of the cylinder at 32791 MPa,which is lower than the permissible strength of the material.The deformation measurement of the flexispline assembly process was measured by the high⁃precision coordinate measuring machine,the axial tooth width interval of the long axis and the short axis was 1 mm as the detection point,and the measurement results were compared with the simulation results to verify.The error results are within 5%,which verifies the applicability of the simulation analysis and provides data support for subsequent harmonic reducer designs.